Community Based Resource Management Training Package - Orirana, Grace; Kenilorea, Peter (MFMR, 2022)
In the Solomon Islands, more than 80% of the population are rural dwellers who commonly build livelihoods from subsistence agriculture and fisheries. Indigenous people own more than 80% of the land including the shorelines. Recognizing this customary land tenure, the Solomon Islands Government has decided that Community Based Resource Management (CBRM) is the main strategy for coastal resource management in the country (sometimes also referred to as CBFM or Community Based Fisheries Management). This CBRM training package aims at improving existing knowledge, understanding, and capacity of provincial fisheries officers (PFO) to support them in their mandated as CBRM facilitators. The PFOs are the lead facilitators in information dissemination in community engagement. Thus, it is vital that PFOs fully understand the various topics and facilitating techniques that are relevant to implementing and scaling CBRM at the community level. This requires PFOs to undertake three to four days training on various topics ranging from fisheries biology to fisheries regulations and applicable activities for conducting awareness and developing community management plans. The modules contain objectives, key messages, content which is structured according to the key messages, assessment, resources, and favorite asked questions (FAQ). Each module would be facilitated by staff of WorldFish and MFMR.